Roses and radicals : the epic story of how American women won the right to vote - Zimet, Susan; Hasak-Lowy, Todd, 1969- (Viking, 2018)
Examines the women's suffrage movement in the United States, highlighting the people who were ridiculed, arrested, tortured, and imprisoned for over seventy years until women were given the right to vote in 1920 with the Nineteenth Amendment. Features sidebars, black-and-white photographs, and biographical sketches.